75.2k views
3 votes
Find the difference of
(3c-d)^2

User Taralex
by
5.5k points

1 Answer

2 votes

Answer:

  • 9c² - 6cd + d²

Step-by-step explanation:

To find the difference (3c - d)² you should recognize that it is the square of a difference of two terms.

The square of the difference of two terms is a special case that you should remember: it is equal to the square of the first, minus twice the product of the first and second, plus the square of the second:

  • (x - y)² = x² - 2xy + y²

For the binomial (3c - d)² you have that:

  • x = 3c
  • y = d

Thus:

  • (3c -d)² = (3c)² - 2(3c)(d) + d² = 9c² -6cd + d² ← answer
User Pawel Czuczwara
by
4.2k points